Digital Sovereignty - Julia Pohle; Thorsten Thiel (Practicing Sovereignty: Digital Involvement in Times of Crises, 2021)
Over the last decade, digital sovereignty has become a central element in policy discourses on digital issues. Although it has become popular in both centralised/authoritarian and democratic countries alike, the concept remains highly contested. After investigating the challenges to sovereignty apparently posed by the digital transformation, this essay retraces how sovereignty has re-emerged as a key category with regard to the digital. By systematising the various normative claims to digital sovereignty, it then goes on to show how, today, the concept is understood more as a discursive practice in politics and policy than as a legal or organisational concept.
Additional information: This article has been first published in Internet Policy Review: Julia Pohle and Thorsten Thiel. 2020. “Digital sovereignty.” Internet Policy Review 9 (4). https://doi.org/10.14763/2020.4.1532
Keywords: 300; digital sovereignty; internet governance; internet exceptionalism; digital economy; state authority